Intraframe Compression Using Lifting Scheme Wavelet-Based Transformation (9/7-Tap Filter) - Mhammad, Aree A. (Sulaimani Journal for Pure and Applied Sciences, 2008)
Image compression is now essential for applications such as transmission and storage in data bases. This paper proposes a new scheme for image compression; this new method involves two steps. First, we use a lifting scheme wavelet-based transform. Second, we develop a modified entropy coding algorithm. We show how block subband coding leads to increase the compression factor with preserving the quality. The main objective of this work is to encode the intra-frame in a video sequences.
Keywords: Anger Frame Compression Color Transformation Lifting SchemeAdaptive Quantization Optimized Shift Coding Quality MeasurementCompression Factor